(untitled) (Journal of Leadership, Accountability and Ethics, 2018)
This case examines the allegations of bribery of government officials by Walmart’s Mexican subsidiary and the subsequent investigation carried out by the U.S. Department of Justice. The primary subject matter of the case is the Foreign Corrupt Practices Act (FCPA) and the potential lack of effective leadership. The case reviews the important components of the FCPA, looks into the specific acts of potentially illegal behavior in Mexico and the United States relative to the incident, and proposes the question of how Walmart could have handled the situation more effectively. The case provides a view into potential pitfalls MNCs encounter when conducting business in developing countries with differing ethical standards.